(untitled) (SAINTEKBU, 2016)
px; "> <Reflection wave by objects (things) that affected phases changing from wave and influenced the power of wave signal. The difference kind of things will give different reflection coefficient. Wave signal that’s happen is depends on the kind of the thing. There are three nature of the object that’s continuing, absorb and reflecting the wave signal. Reflected coefficient with negative value that’s means the object could reflecting the signal and the positive value means the object could absorb or continuing the wave signal. Reflection coefficient data could be saved in a database that its data from kinds of thing in table form could be access anytime its needed, so we can easily to find out the value of reflection coefficient. Process of data relation in database system used SQL as programming language. Keywords: Reflection coefficient, kinds of object, database system, SQL.